Japan's security renaissance : new policies and politics for the twenty-first century - Oros, Andrew (Contemporary Asia in the world., 2017)
For decades after World War II, Japan chose to focus on soft power and economic diplomacy alongside a close alliance with the United States, eschewing a potential leadership role in regional and global security. Since the end of the Cold War, and especially since the rise of Prime Minister Shinzo Abe, Japan's military capabilities have resurged. In this analysis of Japan's changing military policy, Andrew L. Oros shows how a gradual awakening to new security challenges has culminated in the multifaceted "security renaissance" of the past decade. Despite openness to new approaches, however, three historical legacies'contested memories of the Pacific War and Imperial Japan, postwar anti-militarist convictions, and an unequal relationship with the United States'play an outsized role. In Japan's Security Renaissance Oros argues that Japan's future security policies will continue to be shaped by these legacies, which Japanese leaders have struggled to address. He argues that claims of rising nationalism in Japan are overstated, but there has been a discernable shift favoring the conservative Abe and his Liberal Democratic Party. Bringing together Japanese domestic politics with the broader geopolitical landscape of East Asia and the world, Japan's Security Renaissance provides guidance on this century's emerging international dynamics